Psoriasis and its association with metabolic syndrome: A case-Control study at a tertiary care center in a semi-Urban region of South India - Akshay Samagani; Harikishan Kumar Yadalla; P Raju Belliappa (Wolters Kluwer Medknow Publications, 2023)
Background: Metabolic syndrome (MS) has been associated with skin diseases such as psoriasis. They share a common inflammatory pathway and therefore have an impact on each other. Objectives: To estimate the prevalence of MS and its individual components in psoriasis patients to that of the controls and to compare the characteristics in psoriasis patients with and without the MS. Materials and Methods: One hundred patients with a clinical diagnosis of chronic plaque psoriasis were evaluated for the prevalence of MS and compared with the age- and sex-matched controls. Results: The study population belongs to the semi-urban region with a low socioeconomic status. The psoriatic cases showed male preponderance, and the majority of the subjects belonged to 31-40 years of age group. The mean psoriasis area severity index score among cases was 26.19 ± 10.8, and 92% of cases were with severe disease affecting the quality of life. MS was found to be statistically significant in cases. The cases with MS had a higher prevalence of central obesity, hypertriglyceridemia, elevated fasting blood glucose levels, and hypertension. The presence of MS in psoriasis patients was statistically independent of the severity. Conclusions: Psoriasis patients should be periodically evaluated for metabolic syndrome to prevent the associated mortalities and for their effective management.